Analisis Diare dan Demam Berdarah Dengue Ditinjau dari Ketersediaan Tempat Pembuangan Sampah di Komplek Depag, Cipocok Jaya, Kota Serang - Utari, Enggar; Mukrimah, Mukrimah; Zahranie, Laila Rahma; Hidayanti, Savira; Valentini, Valentini (Jurnal Ilmiah IKIP Mataram, 2023)
The limitations of TPS and TPA in the community have resulted in decreased public awareness, causing deviant behavior such as littering, which will cause big problems in the environment, especially problems in helath. The purpose of this study is it to determine the quality of public health in terms of the availability of garbage disposal sites in the ministry of religion complex, Cipocok Jaya, Serang City. The methodin this study uses random sampling and the location is determined based on purposive sampling with consideration to analyze the effect of the presence of TPS and TPA on the quality of publict health. From the results of the study, it can be found that there is a link between the availability of TPS and the quality of public health, this relationship is shown from cases of diarrhea and dengue which reached 38% of the population had experienced and 20% had symptoms of diarrhea and dengue fever, the remaining 42% of people had never experienced cases of diarrhea and dengue fever found in the ministry of religion complax which has limited availability of TPS with environmental conditions that are still was found scattered garbage.